The history of mathematics education in Latin America - Carrillo Gallego, Dolores; Matos, José Manuel; Sánchez Jiménez, Encarna; Rodrigues Valente, Wagner (Historia y Memoria de la Educación, 2019)
Introduction to the Special Issue The history of mathematics education in Latin America